Stent Wear Analysis for Percutaneous Coronary Interventions - Koštialiková, Daniela; Janeková, Mariana; Dubec, Andrej; Kováčiková, Petra (Manufacturing Technology Journal, 2022)
The given paper deals with the issue of materials used in the treatment of heart attacks. In more de-tail it focuses on individual types of stents and their specific properties. The article describes selected groups of biocompatible metal-based materials. Our attention is mainly paid to magnesium alloys. The introduction explains the concept of biocompa-tibility and the distribution of materials accord-ing to their biological tolerance. In the experiment, we performed an ana-lysis of the chemical com-position of individual metal stents and focused on examining their wear resistance. Since it is too difficult to imitate human body environment, we opted for corrosion test for the experiment. Stents were exposed to the given concentration of the solution and temperature. The time period during which the stents were in solution was also important. In the final part, we focused on the microscopic evaluation of the surface.
Keywords: Biocompatibility; Stent; Corrosion; Magnesium alloys